Sams Teach Yourself SQL in 10 Minutes, Second Edition - Forta, Ben (Que, 2001)
Sams Teach Yourself SQL in 10 Minutes, 2E is a tutorial-based book, organized into a series of easy-to-follow, 10-minute lessons. These well targeted lessons teach you in 10 minutes what some books take several hours or days to teach. Instead of dwelling of database theory and relational design, this book takes a very hands-on approach to solving the needs of the majority of SQL users who simply need to interact with data. The reader of this book will learn how to: Retrieve and sort data Filter data using comparisons and wildcards Use the aggregate functions to analyze data Perform insert, update, and delete operations Join relational tables using inner, outer, and self joins Combine queries using unions Use views Create and use stored procedures, triggers, and other advanced database features.